Strategi Manajemen Usaha Pertanian di Desa Masalap Raya Kecamatan Rantau Pulung Kabupaten Kutai Timur - Nursida Nursida; Istikomah Istikomah; Muhamad Yazid Bustomi; Andi Lelanovita Sardianti; Wike Pratiwi; Pandhu Rochman Suosa Putra (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2023)
Every business both retail and agricultural businesses require proper management. From the financial side, how to manage the capital and profits obtained. From the production side, how to produce quality products that consumers want, and other management sides. This activity was carried out at the Meeting Hall of Masalap Raya Village, Rantau Pulung Sub-District, East Kutai District. This area is one of the transmigration areas where there is still a lot of agricultural lands. Various types of commodities grown in this area include food crop agriculture, oil palm crops, animal husbandry, and other agricultural sectors. This activity was attended by farmers and several village leaders who participated in supporting this activity. The activity ran smoothly as seen from the enthusiasm of the participants during the question and answer session. This activity is expected to help farmers in managing their businesses and think about how to get to develop the business and keep it consistent and sustainable. The activity ended with a group photo session between the resource persons and participants as well as local village officials.